Association of the angiotensin I converting enzyme (ACE) gene polymorphisms with recurrent aphthous stomatitis in the Czech population: case-control study - Julie Bartakova; Tereza Deissova; Simona Slezakova; Jirina Bartova; Jitka Petanova; Pavel Kuklinek; Antonin Fassmann; Petra Borilova Linhartova; Ladislav Dušek; Lydie Izakovicova Holla (BMC, 2022)
Abstract Background Recurrent aphthous stomatitis (RAS) is multifactorial disease with unclear etiopathogenesis. The aim of this study was to determine distribution of the angiotensin I converting enzyme (ACE) gene polymorphisms and their influence on RAS susceptibility in Czech population. Methods The study included 230 subjects (143 healthy controls and 87 patients with RAS) with anamnestic, clinical and laboratory data. Five ACE gene polymorphisms (rs4291/rs4305/rs4311/rs4331/rs1799752 = ACE I/D) were determined by TaqMan technique. Results The allele and genotype distributions of the studied ACE I/D polymorphisms were not significantly different between subjects with/without RAS (P corr > 0.05). However, carriers of II genotype were less frequent in the RAS group (OR = 0.48, 95% CI = 0.21-1.12, P = 0.059). Stratified analysis by sex demonstrated lower frequency of II genotype in women (OR = 0.33, 95% CI = 0.09-1.17, P < 0.035, P corr > 0.05, respectively) than in men with RAS (P > 0.05). Moreover, the frequency of AGTGD haplotype was significantly increased in RAS patients (OR = 13.74, 95% CI = 1.70-110.79, P = 0.0012, P corr < 0.05). In subanalysis, TGD haplotype was significantly more frequent in RAS patients (P < 0.00001) and CGI haplotype was less frequent in RAS patients (P < 0.01), especially in women (P = 0.016, P corr > 0.05). Conclusions Our study indicates that while the AGTGD and TGD haplotypes are associated with increased risk of RAS development, CGI haplotype might be one of protective factors against RAS susceptibility in Czech population.